112k views
8 votes
(x+y)2-2(x+y)(a+x)+(a+x)2

User Layonez
by
7.8k points

1 Answer

12 votes

Answer:

2ax−2ay−2x2−2xy+2a+4x+2y

Explanation:

Let's simplify step-by-step.

(x+y)(2)−2(x+y)(a+x)+(a+x)(2)

Distribute:

=(x)(2)+(y)(2)+−2ax+−2ay+−2x2+−2xy+(a)(2)+(x)(2)

=2x+2y+−2ax+−2ay+−2x2+−2xy+2a+2x

Combine Like Terms:

=2x+2y+−2ax+−2ay+−2x2+−2xy+2a+2x

=(−2ax)+(−2ay)+(−2x2)+(−2xy)+(2a)+(2x+2x)+(2y)

=−2ax+−2ay+−2x2+−2xy+2a+4x+2y

Answer:

=−2ax−2ay−2x2−2xy+2a+4x+2y

User FrankieTheKneeMan
by
7.7k points